Rancang Bangun MyAKAD Apps Berbasis Android Menggunakan Algoritma Sequential Searching - Wahyu Mahatma Kurniawan; Fauziah Fauziah; Aris Gunaryati (STMIK Budi Darma, 2020)
The existence of the digital world has given a new impact to all human activities. Not surprisingly, if now all switch to the digital world because on the one hand can make things more efficient and practical. The purpose of this study, the author wants to develop a student data administration application that will be applied at one of the universities with an Android-based platform system. Where this design is made to perfect the limitations of applications that have previously been developed, namely the web, limitations of previous applications at the University, when users (users) access to the online academic menu in the web application, are required to deactivate pop-ups first, that is felt to be inefficient . Based on the existing problems, the author wants to design an application that will be developed on the Android platform by using a sequential searching algorithm for each program function in the application. The system development method itself uses the Waterfall methodology. This method has stages namely: Analysis, Design, Coding and Testing Data collection techniques are obtained from the results of observations (observations) and literature studies. Database as a data storage medium is MySQL. For the PHP and Java programming languages used as an application interface, the application test results are represented in the White box testing and show a valid value of the test results amounting to 6 in the total decision shows the algorithm used is quite good and meets the standard